1962
DOI: 10.1099/00221287-27-1-121
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Certain Heterotrophic Polarly Flagellate Water Bacteria: Aeromonas, Pseudomonas and Comamonas

Abstract: SUMMARYSixty-one polarly flagellate bacteria, initially identified as such by the type of motility they displayed, were isolated from surface waters and classified on the basis of cultural and biochemical tests into three genera : Aeromorcas, Pseudomonas, Comamonas. Sixteen similarly flagellated cultures from other sources were also found to be members of these genera. Some bacteria with a single polar flagellum and giving reactions of the Alcaligenes type were isolated. It is suggested that the definition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

1964
1964
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…The genus Aeromonas consists of oxidase positive, facultatively anaerobic, polarly flagellated or nonmotile, straight rods which ferment glucose with or without the production of gas (18,19,41). One species carries out a 2,3-butyleneglycol fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Aeromonas consists of oxidase positive, facultatively anaerobic, polarly flagellated or nonmotile, straight rods which ferment glucose with or without the production of gas (18,19,41). One species carries out a 2,3-butyleneglycol fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…1.7003 ± 0.0010 41.1 ± 1.0% (4) 1.7125 ± 0.0006 53.6 ± 0.6% (4) I cr, Curved rod; sr, straight rod.°M ean of two determinations; strains 8 and 40, four analyses; strains 2 and 19, 3 analyses each. c Number of analyses for group.…”
Section: Discussionmentioning
confidence: 99%
“…Serious difficulties also lie in differentiation of Vibrio spp. from the anaerogenic Aeromonas (Park, 1962).…”
mentioning
confidence: 99%
“…The type strains of the latter three species were strains NCIB 2581, NCIB 8194 (= ATCC 6972), and NCIB 2582 (= ATCC 14636), respectively (41,56). Later, it was shown that classification of these organisms as Vibrio species was erroneous, not only because of their aberrant physiological and morphological characteristics (11,14,29,35,52,54) but also because the deoxyribonucleic acid (DNA) base compositions of these strains are considerably higher than those of other Vibrio species (12, 53). Galarneault and Leifson (29) proposed the name 'Lophomonas alcaligenes" for a group of gram-negative, rod-shaped, lophotrichous bacteria which did not attack carbohydrates either fermentatively or oxidatively .…”
mentioning
confidence: 99%